The Role of Meta AI WhatsApp in Enhancing English Reading Skills of Higher Education - Susilowati, Diana; Zainuddin, Zainuddin; Islam, Raudhatul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aimed to explore the role of Meta AI WhatsApp as a technological tool for enhancing English reading skills in higher education. A descriptive qualitative research design was employed, utilizing interviews and open-ended questionnaires to gather in-depth data. The research was conducted with students from the English Education Department at Zainul Hasan Genggong Islamic University. Five participants were purposively selected based on their relevant experience and willingness to participate. The findings showed that Meta AI WhatsApp supported reading comprehension through several key features, including automatic translation, grammar correction, and interactive question-and-answer sessions. Additionally, the platform was found to increase students’ motivation and engagement with English texts. The study also identified several challenges, including answers that are too general, a lack of voice features, and dependence on internet access. Despite these limitations, the study highlights the potential of Meta AI WhatsApp to serve as an effective supplementary tool in language learning. It is recommended that future developments incorporate features such as adjustable difficulty levels and text-to-speech functionality to further enhance its educational value.